Development of a molecular bioswitch using fluorescence lifetime imaging: Incremental activation of fluorescein diacetate. Issue 2 (31st July 2017) - Barnoy, Eran A.; Popovtzer, Rachela; Fixler, Dror
Abstract : Molecular bioswitches offer an invaluable asset in the shift from systemic to targeted treatments. Within the growing arsenal of switches are imaging probes that functionalize only in given locations or situations. Acetate esters are a common fluorescent example, known to activate upon interaction with esterases. Fluorescein diacetate (FDA) is one such fluorophore used in cell viability assays. These assays rely on the fact that the compound begins colorless and with no fluorescent signature whatsoever, and only after internalization into cells it is possible to detect a fluorescence signal. In this study, using fluorescence intensity (FI) and fluorescence lifetime (FLT) imaging, FDA is shown to be fluorescent even when unactivated. Furthermore, the FLT is shown to change with pH. Finally, the ability to image FDA in different environments simulated by tissue‐imitating phantoms is explored. Altogether, the ability of FDA to serve as a bioswitch when measured using FLT imaging microscopy (FLIM) is assessed. The combination of a spectrum of FDA activation and FLIM serves as a bioswitch, where biologically relevant stimulation can generate detectable and incremental variations. Abstract : The fluorescence lifetime of FDA changes incrementally with pH until it reaches full activation.